2019
DOI: 10.1080/2162402x.2019.1656502
|View full text |Cite
|
Sign up to set email alerts
|

Lurbinectedin synergizes with immune checkpoint blockade to generate anticancer immunity

Abstract: Systemic treatment with the active transcription inhibitor lurbinectedin aims at inducing tumor cell death in hyperproliferative neoplasms. Here we show that cell death induced by lurbinectedin reinstates and enhances systemic anticancer immune responses. Lurbinectedin treatment showed traits of immunogenic cell death, including the exposure of calreticulin, the release of ATP, the exodus of high mobility group box 1 (HMGB1) and type 1 interferon responses in vitro. Lurbinectedin treated cells induced antitumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…Beyond a direct cytotoxic effect on tumor cells, its antitumor activity relies also on the depletion of TAMs (in a range from 30 to 77% as observed in clinical studies) through induction of apoptosis [22]. Structurally and functionally similar to trabectidin, lurbinectedin has shown promising clinical results in the treatment of small cell lung cancer, alone or in combination with checkpoint inhibitors or conventional chemotherapeutics [23,24]. Another class of drugs that showed secondary efficacy in depleting TAMs when used in chemotherapeutic regimens, are bisphosphonates, originally developed as inhibitors of osteoclastic bone resorption, now used in both hematological and solid tumors to contrast bone metastases and skeletal negative events [25].…”
Section: Strategies Aimed At Tam Depletionmentioning
confidence: 99%
“…Beyond a direct cytotoxic effect on tumor cells, its antitumor activity relies also on the depletion of TAMs (in a range from 30 to 77% as observed in clinical studies) through induction of apoptosis [22]. Structurally and functionally similar to trabectidin, lurbinectedin has shown promising clinical results in the treatment of small cell lung cancer, alone or in combination with checkpoint inhibitors or conventional chemotherapeutics [23,24]. Another class of drugs that showed secondary efficacy in depleting TAMs when used in chemotherapeutic regimens, are bisphosphonates, originally developed as inhibitors of osteoclastic bone resorption, now used in both hematological and solid tumors to contrast bone metastases and skeletal negative events [25].…”
Section: Strategies Aimed At Tam Depletionmentioning
confidence: 99%
“…Intrigued by this observation, we used multiple tests to measure RNA synthesis (and downstream protein synthesis, downstream of RNA transcription) to conclude that most ICD inducers (including anthracyclines, oxaliplatin, lurbinectedin, crizotinib and thiostrepton) actually cause an inhibition of DNA-to-RNA transcription (and hence a subsequent inhibition of RNA-to-protein translation) and that this effect may cause a peculiar ER stress response consisting in the phosphorylation of eIF2α by eIF2α kinase 3 (EIF2AK3, better known as PERK) without any other signs of the unfolded stress response such as activation of the ATF6 and the IRE1-XBP1 axes. 8 10 The aforementioned results suggest that a vast class of ICD inducers (with the exception of microtubular poisons such as vinca alkaloids and taxanes) is able to reduce RNA synthesis, which resembles a response to viral infection. This has two major implications.…”
mentioning
confidence: 99%
“…A study showed that lurbinectedin treatment could induce ICD traits, such as calreticulin exposure, INF-I immune responses, ATP release, and the exodus of HMGB1 molecules, at in vitro condition. The anticancer and antineoplastic properties of lurbinectedin could be strengthened remarkably by its combination with the double blockade of CTLA-4 and PD-1 immune checkpoints [242]. In another study, conducted by Zhao et al, it was revealed that irreversible electroporation (IRE) combined with anti-PD-1 could significantly induce the ICD process and also mediate the consequence durable response in a treated model (orthotopic pancreatic ductal adenocarcinoma (PDAC)).…”
Section: Therapies Combining Chemotherapy-induced Icdmentioning
confidence: 99%